Development and Validation of RP-HPLC Method for the Simultaneous Estimation of Cedazuridine and Decitabine by in Bulk and its Pharmaceutical Dosage Form - Dharmamoorthy, Dr. G. (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: A new sensitive accurate and precise reverse-phase high-performance liquid chromatography (RP-HPLC) method was developed for the simultaneous estimation of cedazuridine and decitabine in bulk and pharmaceutical formulation. Materials and Methods: Chromatographic separation was achieved through Altima C18 column (4.6*150 nm, 5 μm) using 0.01 Kh2PO4:acetonitrile (60:40 v/v) mixture used as the mobile phase. The Waters 2695, Reciprocating Water-510 pump system with PDA detector, and EMPOWERPRO software were monitored at detection wavelength 257 nm on flow rate 1 mL/min and the method was validated as per ICH guidelines (ICH,Q2 [R1]). Results and Discussion: Cedazuridine and decitabine were eluted at 2.248 min and 2.956 min, respectively, with good resolution. Plate count and tailing factor were very satisfactory, so this method was optimized and to be validated. Conclusion: This RP-HPLC method was successfully applied for the simultaneous determination of cedazuridine and decitabine in their pharmaceutical formulation and, hence, can be used for the routine analysis of these drugs in combined dosage form.